Art and intention: a philosophical study - Livingston, Paisley (Clarendon, 2005)
Do the artist's intentions have anything to do with the making and appreciation of works of art? In 'Art and Intention' Paisley Livingston develops a broad and balanced perspective on perennial disputes between intentionalists and anti-intentionalists in philosophical aesthetics and critical theory